A UK national audit of the laboratory investigation of phaeochromocytoma and paraganglioma. (January 2022) - Boot, Christopher; Toole, Barry; Harris, Sharman; Tetlow, Lisa; Wassif, Wassif S
Background: Phaeochromocytomas and paragangliomas (PPGL) are catecholamine secreting tumours associated with significant morbidity and mortality. Timely diagnosis and management are essential. A range of laboratory tests can be utilised in the investigation of PPGL. There is scope for significant variation in practice between centres. We aimed to investigate how the laboratory investigation of PPGL is performed in laboratories across the United Kingdom. Methods: A questionnaire consisting of 21 questions was circulated to Clinical Biochemistry laboratories in the United Kingdom via the Association for Clinical Biochemistry and Laboratory Medicine office. The survey was designed to allow audit against Endocrine Society Guidelines on the Investigation and Management of PPGL and to obtain information on other important aspects not included in these guidelines. Results: Responses were received from 58 laboratories and the data were compiled. The majority of laboratories use either urine or plasma metanephrines in first-line testing for PPGL, although a number of different combinations of biochemistry tests are utilised in different centres. All laboratories measuring metanephrines or catecholamines in-house use LC or LC-MS/MS methods. There are some marked differences between laboratories in urine metanephrines reference ranges used and sample requirements. Conclusions: There is evidence of good practice in UK laboratories (as assessed against Endocrine Society Guidelines) such as widespread use of urine/plasma metanephrines and appropriate analytical methodologies used. However, there is also evidence of variations in practice in some areas that should be addressed.